Different Perspectives in Wendelin Van Draanen’s “Flipped”: Different perspective, Psychological Approach, Psychodynamic Perspective, Cognitive Perspective, and Cross-Culture Perspective. - Mantiri, Silvia; Mamentu, Agustine; Kamagi, Sarah (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research aims to analyze the differences in the perspectives of the main characters in Wendelin van Draanen's novel Flipped. It uses qualitative methods, in which the results are in the form of words. The researcher collected data sources into two categories: primary and secondary sources. The primary data was collected from the Flipped novel, and the secondary data was collected from articles, journals, e-journals, books, e-books, and other sources. The researcher uses a psychological approach especially Sigmund Freud's psychoanalytic theory (1933) to analyze the differences in perspective between Brice and Juli as adolescents. Freud pointed out that early childhood events influence a big part of our mental lives and occur outside of our conscious knowledge. The researcher identified numerous differences in perspectives that affect Brice and Juli's thoughts and behavior as mentally unstable adolescents. The researcher classified these perspectives based on psychological perspectives; the researcher found psychodynamic, cognitive, and cross-cultural perspectives. The occurrence they experienced had an enormous effect on their life. When Brice was a child, he didn't like July, but as he became an adolescent, he started to appreciate Juli—Bryce flipped as Juli had done previously. Brice understands that Juli's charisma and personality set her apart from the other girls. On the other hand, Juli learned to control her feelings for Brice, and she was no longer as fixated on Brice as she had been as a child. Juli has become more focused on herself and her family as she grows.